Does abuse in late life worsen sleep quality? A two-year prospective cohort study among rural older adults - Yunus, Raudah Mohd; Hairi, Noran Naqiah; Choo, Wan Yuen; Sooryanarayana, Rajini; Hairi, Farizah Mohd; Ismail, Norliana; Kandiben, Shathanapriya; Tey, Nai Peng; Ali, Zainudin Mohd; Ahmad, Sharifah Nor; Razak, Inayah Abdul; Othman, Sajaratulnisah; et al. (John Wiley & Sons, 2018)
Background: Elder abuse and neglect (EAN) is a growing public health problem, and numerous adverse health effects of abuse in late life have been documented. Little is known, however, about the impact of elder abuse on sleep quality. This study examines the longitudinal relationship between EAN and sleep quality. Methods: This was a 2-year prospective cohort study involving 1927 older adults in a rural Malaysian district, Kuala Pilah. A multi-stage cluster sampling strategy was employed. After 2 years, 1189 respondents were re-assessed. EAN was determined using the modified Conflict Tactic Scale, while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Results: The prevalence of elder abuse was 8.1% (95% CI:6.9,9.3). Longitudinal analysis using generalized estimating equations showed that elder abuse contributed to higher PSQI scores (B:0.49, 95% CI:0.17,0.58). Sub-analyses demonstrated that psychological abuse and neglect had significant longitudinal relationships with increase of PSQI scores, while other subtypes did not. Conclusion: Abuse in late life, particularly psychological abuse and neglect, result in greater PSQI scores. Even though this may imply decline in sleep quality, our findings were not considered clinically significant as they did not exceed the clinical cut-off score of five. Nevertheless, sleep quality is an important determinant of health and a predictor of mortality among older adults; thus, understanding its relationship with abuse is useful to health care providers and policy-makers in improving health services and upgrading preventive measures.